(untitled) (Encuentros, 2016)
The result of a qualitative descriptive study of a convenience sample, which had the main objective is presented below: “To analyze the social representations about the role of the family that built the four district schools teachers in Bogota”. For this article the results of the FDI Miguel Antonio Caro Bogota, where part (20) twenty teachers with their stories about their work everyday are socialized. Understanding these social representations allows us to understand the reasons why they fail or integration strategies are right family to school in a public institution. Keywords: Social representations, Family, School, Teachers.